PEMARKAH PERTARAFAN DALAM BAHASA SUNDA - Yayat Sudaryat (Adabiyyāt: Jurnal Bahasa dan Sastra, 2013)
Sundanese. It uses the descriptive method. The data were This research aims to describe the qualitative marker in collected with bibliographic study, intuitive technique, and elicitation technique. The sources of data are the spoken and written Sundanese and its variation. The data are analyzed with distributional method and immediate constituent analysis. The result shows that there are 32 the qualitative markers in Sundanese: two affixes and thirty qualitative adverbs. The result of this study consists of four qualitative markers. They are form, distribution, function, and meaning. The form of the qualitative marker consists of four word forms: the simple words, derivative words, reduplication words, and compound words. The distribution of the qualitative marker in adjective phrases consists of four word positions: pre-adjective, postadjective, pre-post-adjective, and mobile position. The function of the qualitative marker consists of two kinds of functions: the inflective function and attributive function. The meaning of the qualitative marker consists of two quality degree. The first is quality degree which divides at positive, intensive, elative, excessive, augmentative, and extenuative. The second is a comparison degree which divides at equative, comparative, and superlative.